High Resolution CT Chest Findings in PCR Positive or Clinically Suspected patients of Covid-19 Infection - Maimoona Gulshan, Syeda Khadija Ejaz, Mehwish Tahir, Attka Maryam, Sadaf Qadir, Zafar Rafique (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: HRCT chest findings in PCR positive or clinically suspected patients of COVID-19 infection. Methods: Retrospective study recruited 207 clinically suspected patients of COVID disease with duration of 1-14 days from the radiology department of Shalamar Hospital Lahore. Patients were categorized into two groups on the basis of PCR +ve (123) and PCR -ve group (84). Results: Among 123 PCR +ve patients, 107 patients were CT Positive and 16 were CT negative. While from 84 PCR -ve patients, 38 patients were CT positive. Among PCR Positive patients, most prevalent finding was GGO (84.5%), followed by lymphadenopathy(48.8%), interlobular septal thickening (41.5%), consolidation (5.7%) on HRCT chest. The GGO was mostly bilateral (82.2%) and Peripheral (47.8%). Among 84 PCR negative patients, GGO (45.3%), followed by interlobular septal thickening (28.6%), lymphadenopathy (19.1%). The GGO was mostly bilateral (26.2%) and Peripheral (25%). HRCT Chest has Sensitivity (86%), specificity (54%) and accuracy 74%. Conclusion: GGOs with bilateral and peripheral distribution was the most common finding in both PCR positive and negative patients, whereas lymphadenopathy in PCR positive and Interlobular septal thickening in PCR negative patients was the second common finding. High resolution CT Chest performs a significant role in early diagnosis of patients with COVID-19 due to its high sensitivity and specificity.